THE REMODELING OF LEFT VENTRICULAR MYOCARDIUM IN PATIEMTS WITH 4 KIND OF CHRONIC CARDIORENAL SYNDROME - Kurchubadze, E.; Vlasenko, M. A.; Vlasenko, O. O. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Myocardial remodeling of left ventricular is examined in 107 patients of chronic kidney desease (CKD) with arterial hypertension of II–III stages: 54 chronic glomerulonephritis, 36 — chronic pielonephritis and 17 diabetic nephropathy. CKD was established of I stage (st) in 42 patients, II st — in 20 patients, III st in 27 patients and IV st in 18 patients. The formation of cardiorenal syndrome in patients with nephrogenic arterial hypertension is manifested by myocardial remodeling of the left ventricle with concentric hypertrophy. It is developed during early stage of chronic kidney disease meanwhile excentric hypertrophy of left myocardial ventricle is appeared with progression of chronic kidney disease.